Modeling and Simulation Tools for Emerging Telecommunication Networks Needs, Trends, Challenges and Solutions - Nejat Ince, A.; Topuz, Ercan; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
This book contains a selection of papers presented at a symposium organized under the aegis of COST Telecommunications Action 285. The main objective of the Action is to enhance existing tools and develop new modeling and simulation tools for research in emerging multi-service telecommunication networks in the areas of model performance improvements, multilayer traffic modeling, and the important issue of evaluation and validation of the new modeling tools. The studies related to the activities above are carried out by members of the Action Group with contributions from invited experts/scientists from non-COST country academia and industry (within and outside Europe) when deemed necessary. The book in your hands is the collection of some important aspects of study results achieved by this mixed group of experts/scientists from Europe and the United States of America. The symposium presentations were made in four sessions as follows: 1. Multilayer Traffic and Mulimedia Behavior, 2. Quality of Simulations, 3. Accelerated Simulation Methods, 4. Verification, Validation and Credibility of Simulations, and covered nearly all of the important aspects of the subjects and issues above. It is hoped and expected that this book will be useful as a reference work for practicing engineers as well as academic researchers. .
European Concerted Research Action COST 285 Modeling and Simulation Tools for Research in Emerging Multiservice Telecommunications -- Challenges in Design of Next Generation Networks -- An Empirical Approach For Multilayer Traffic Modeling And Multimedia Traffic Modeling At Different Time Scales -- Multimedia Traffic Behavior: Analysis and Implications -- Traffic Modeling and Prediction using ARIMA/GARCH Model -- On the Scalability of Fluid Models of IP Networks Loaded by Long-lived TCP Flows -- The Optimal Dimensioning Of Multi-Service Links -- A Network Management Framework for Emerging Telecommunications Networks -- Challenges of Tool Development Facing Rapidly Changing Market Demands -- Packaging Simulation Results With CostGlue -- Modeling Grids in (Near) Real Time -- Network Simulator NS2: Shortcomings, Potential Development and Enhancement Strategies -- Integrated Simulation of Communication Networks and Logistical Networks -- Evaluating Vehicular Networks: Analysis, Simulation, and Field Experiments -- A Monte Carlo Type Simulation Approach For Performance Evaluation In Optical Burst Switched Networks -- Simulation of Radio Channel and Modulation Schemes Using Markov Chains -- A Component Approach to Optical Transmission Network Design -- Fast Dimensioning of Packet-Switched All-Optical Networks -- Quality Assessment of Modeling and Simulation of Network-Centric Military Systems -- Using Fuzzy Value Tree Analysis to Support The Verification, Validation, and Accreditation of Models and Simulations -- On The Use Of Simulation For The Improvement And Measurement Validation Of A Smart Antenna Prototype -- The Need for Credible Modeling and Simulation in the Context of the Network Based Defense -- An Analysis Tool for Markovian Traffic Model Validation -- Some General Terminal and Network Teletraffic Equations for Virtual Circuit Switching Systems.
Keywords: Computer science; Computer communication systems; System theory; Electrical engineering; Computer Science; Computer Communication Networks; Communications Engineering, Networks; Electrical Engineering; Systems Theory, Control; Signal, Image and Speech Processing; Electronic books